The languages and linguistics of indigenous North America, volume 2 a comprehensive guide - Dagostino, Carmen; Mithun, Marianne 1946-; Rice, Keren 1949- (De Gruyter Mouton, 2024)
This handbook provides broad coverage of the languages indigenous to North America, with special focus on typologically interesting features and areal characteristics, surveys of current work, and topics of particular importance to communities. The volume is divided into two major parts: subfields of linguistics and family sketches. The subfields include those that are customarily addressed in discussions of North American languages (sounds and sound structure, words, sentences), as well as many that have received somewhat less attention until recently (tone, prosody, sociolinguistic variation, directives, information structure, discourse, meaning, language over space and time, conversation structure, evidentiality, pragmatics, verbal art, first and second language acquisition, archives, evolving notions of fieldwork). Family sketches cover major language families and isolates and highlight topics of special value to communities engaged in work on language maintenance, documentation, and revitalization
Keywords: Linguistik; Nordamerika; Sprache; FOREIGN LANGUAGE STUDY / Native American Languages